SYNTHESIS AND ANTICONVULSANT ACTIVITY (CHEMO SHOCK) OF N-1(SUBSTITUTED-N-4[(4-OXO-3-PHENYL-3, 4-DIHYDRO-QUINAZOLINE-2-YLMETHYL) SEMICARBAZONES - Yadav, Meena K; Tripathi, Laxmi; Goswami, Diptendu (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: This work is designed at finding new structure leads with potential anticonvulsant activities of 4(3H)-quinazolinone pharmacophore scaffold. Methods: A new series of 4(3H)-quinazolinone pharmacophore was designed with substituted moieties possesses different electronic environment in the hope of developing potent and safe new effective compounds. In such fashion, in this paper, we report the synthesis and anticonvulsant activity (Chemo shock) of N-1(substituted-N-4[(4-oxo-3-phenyl-3, 4-dihydro-quinazoline-2-ylmethyl) semicarbazones 3A-d (1-7), 3B-d (1-7), 3C-d (1-7), their chemical structure were characterized using IR, H-H NMR, and elemental analysis techniques. Their anticonvulsant activity was evaluated using chemicals strychnine, thiosemicarbazide and 4-aminopyridine induced seizure models at a dose of 30, 100, 300 mg/kg unto 2 hrs tests in mice. The rotarod assay was performed in mice to evaluate the neurotoxicity of the compounds. 1 Results: Compounds 3C (d-4), 3B (d-4), and 3A (d-4) were observed to be most feasible to act against glutamate receptor for anticonvulsant activity. Conclusions: The results obtained revealed that numbers of novel quinazolinone semicarbazone derivatives are effective in chemical to induce (chemo shock) model and showing good anticonvulsant activity. Keywords: Quinazolinone, Semicarbazones, Strychnine, Thiosemicarbazide, 4-aminopyridine, Anticonvulsant activity, Chemo shock.